2022
DOI: 10.2991/assehr.k.220105.008
|View full text |Cite
|
Sign up to set email alerts
|

The Advantages and Disadvantages of Learning a Second Language Early

Abstract: With the accelerating of the worldwide favor of learning a second language, this article illustrates the advantages and disadvantages of learning a second language early by analysing relevant research and articles. The advantages of learning a second language are based on the prefrontal cortex in the brain that can help promote the cognitive development like attentional ability, memory and creativity. The acquisition of a second language can in fact benefit from the cognitive development and the academic devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…In contrast to years of living in the USA, it founded that age at the time of immigration had a significant impact on English proficiency level. Younger immigrants were more likely than older ones to reach native language competency levels [4]. In another study by Patkowski [5] that 67 immigrants educated in the USA, this study found some similar findings that those who immigrated to the USA before the age of 15 were more skilled use English than those who immigrated after the age of 15 [5] Apart from that, Cummins and Nakajima [6] also surveyed 273 Japanese children who had immigrated to Toronto and found that immigrants' reading and writing levels of foreign languages strong increased with age, this could be occurred because older immigrants benefited more from their previous cultural experiences.…”
Section: The Second Language-learning Ability At An Early Stagementioning
confidence: 97%
See 1 more Smart Citation
“…In contrast to years of living in the USA, it founded that age at the time of immigration had a significant impact on English proficiency level. Younger immigrants were more likely than older ones to reach native language competency levels [4]. In another study by Patkowski [5] that 67 immigrants educated in the USA, this study found some similar findings that those who immigrated to the USA before the age of 15 were more skilled use English than those who immigrated after the age of 15 [5] Apart from that, Cummins and Nakajima [6] also surveyed 273 Japanese children who had immigrated to Toronto and found that immigrants' reading and writing levels of foreign languages strong increased with age, this could be occurred because older immigrants benefited more from their previous cultural experiences.…”
Section: The Second Language-learning Ability At An Early Stagementioning
confidence: 97%
“…Oyama conducted sixty immigration interviews in the US. The ages of immigrants range from six to twenty, and their stays in the nation typically last five to eighteen years [4]. In contrast to years of living in the USA, it founded that age at the time of immigration had a significant impact on English proficiency level.…”
Section: The Second Language-learning Ability At An Early Stagementioning
confidence: 99%
“…As Marion and Shook (2012) reported, people who speak more than one language can perform better on tasks that need conflict management. Zhang (2021) added that being bilingual or multilingual can make someone see a situation from another perspective besides helping the person increase his international trade opportunities. Apart from the advantages, many FL learners still experience anxiety in the classroom due to several reasons, which are communication apprehension, test anxiety and fear of negative evaluation.…”
Section: Problem Statementmentioning
confidence: 99%
“…The need for in-depth research on metacognitive methods for effective learning, especially in the context of learning a second language (L2), has emerged from the study of existing literature on their impact on language learners (e.g., Zhang & Guo, 2020;Raoofi et al, 2014). This involves vocabulary acquisition strategies in which they can be classified into different taxonomies, such as social, memory, cognitive, and metacognitive, or determination and consolidation strategies.…”
Section: Introductionmentioning
confidence: 99%